1989
DOI: 10.1001/archotol.1989.01860280098025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Albumin-Bound Furosemide on the Endocochlear Potential of the Chinchilla: Alleviation of Furosemide-Induced Ototoxicity

Abstract: \s=b\The effects of albumin-unbound furosemide and albumin-bound furosemide on the cochlear function were compared by the continuous observation of the endocochlear potential (EP) in the chinchilla using the microelectrode method. The EP depression following the intravenous injection of 50 mg/kg of furosemide was 108.5 \m=+-\2.7 mV, while the addition of 1.0 and 1.3 g/kg of albumin induced the EP depression to be 35.0 \m=+-\4.8 and 8.1 \ m=+-\ 1.9 mV, respectively, and both prolonged the time to attain the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The transient nature of furosemide effects have been shown to last for hours 10,11 but certainly not for 7 days, which is the longest survival time we examined. In addition, we have shown here that the EP in normal animals that receive the conditioning treatment can recover.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The transient nature of furosemide effects have been shown to last for hours 10,11 but certainly not for 7 days, which is the longest survival time we examined. In addition, we have shown here that the EP in normal animals that receive the conditioning treatment can recover.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, we have shown here that the EP in normal animals that receive the conditioning treatment can recover. Thus, once the effects of furosemide subside and the SV regains its function, potassium levels in the SM begin to recover and return to normal within hours [11][12][13] as does the EP. [13][14][15] Our finding that implanted cells survive despite the return of a potassium rich fluid around them suggests that gradual return to normal conditions in SM is compatible with survival of transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since a single injection of furosemide at an appropriate time (30 minutes) before the broadband noise exposure (but not after) was effective in providing protection, it is likely that the protective effect of furosemide is related to its reversible depression of the endocochlear potential [14], which is one of the main electrochemical gradients required for auditory transduction, and reduction in the magnitude of the endocochlear potential. This leads to depression of the cochlear amplifier [15], with smaller active displacements of the outer hair cells (OHCs) [16] within a short period after its injection.…”
Section: Discussionmentioning
confidence: 99%
“…Diuretic-induced inhibition of the Na-K-2Cl cotransport system in the ascending limb of Henle's loop in the kidney suggested that this cotransporter might play an important role in the stria ( Burg et al., 1973 , Sellick and Johnstone, 1975 , Shindo et al., 1992 ). Indeed, many studies indicate that diuretics and anoxia affect the Na-K-2Cl cotransporter in strial marginal cells ( Bosher, 1979 , Bosher, 1980 , Ikeda and Morizono, 1989b , Ikeda and Morizono, 1989c , Ikeda and Morizono, 1989a , Shindo et al., 1992 , Xu et al., 1994 , Wangemann et al., 1995 , Ikeda et al., 1997 ), however, inhibition of this cotransporter occurs much later that the immediate reduction of EP ( Bosher, 1980 ).…”
Section: Possible Ototoxic Mechanisms Of Loop Diureticsmentioning
confidence: 99%